South european welfare regimes and the impact of 2007 crisis on Spain welfare - Culfaz, Eylul (Papeles de Europa, 2014)
This article analyzes the Southern European countries (Spain, Greece, Italy and Portugal) as participants of a specific model of welfare and considers Spain as representative of the model. As a result of 2007 crisis, the Spanish economy has been affected deeply and also shows deformation in its welfare system. The private sector weakens in providing the welfare while public sector and families take most of the burden of society through the social protection system and solidarity networks. However both families-with decreasing personal and household income, and rising rates of unemployment, and the state-with rising tensions over its public finances, can not fulfill their important role in maintenance of the regime, which can provoke a change in its welfare model.
Keywords: welfare regimes; South Europe; economic crisis